Aktuální pohled na možnosti diagnostiky a léčby diabetu typu LADA - Urbanová, Jana; Brunerová, Ludmila; Malinovská, Jana; Pelechová, Barbora; Koberová, Ludmila; Brož, Jan (Vnitrni lekarstvi, 2021)
Latent Autoimmune Diabetes in Adults (LADA) is an autoimmune disease arising at adulthood. LADA is characterized by a less intensive autoimmune process, slower progression and a mild metabolic decompensation at onset compared with young-onset type 1 diabetes mellitus. The onset of LADA is usually in non-obese patients over 30, without prominent features of metabolic syndrome and insulin resistance. Nevertheless it may be falsely classified as type 2 diabetes, especially, when diagnosed in older age and for the possibility of non-insulin treatment for at least 6 months after diagnosis. LADA is treated early with insulin and combined with metformin in patients with a higher level of insulin resistance. Clinical studies suggested also effectivity of other oral antidiabetics enabling preservation of residual β-cell function, such as particularly incretines.
Keywords: senioři; glutamát dekarboxyláza; diabetes mellitus; GADA; diabetes mellitus 1. typu; Diabetes Mellitus, Type 2; latentní autoimunitní diabetes dospělých; type 2 diabetes; Adult; Glutamate Decarboxylase; diabetes mellitus 2. typu; hypoglykemika; Diabetes Mellitus, Type 1; Humans; Latent Autoimmune Diabetes in Adults; therapy; autoprotilátky; LADA; diagnosis; cardiovascular disease; dospělí; Aged; Hypoglycemic Agents; Autoantibodies; lidé